A qualitative study of same session co-use of nicotine and cannabis among adolescents and young adults - Danielle R. Davis; Dana A. Cavallo; Krysten W. Bold; Meghan E. Morean; Grace Kong; Wei Li; Vanessa Ponte; Nicholas Franco; Sarah Lichenstein; Suchitra Krishnan-Sarin (PLoS ONE, 2026)
Purpose Nicotine and cannabis are commonly co-used among adolescents and young adults (AYAs). Same session co-use has more negative effects than co-use that does not overlap. Little is known about how or why these products are used within the same session. Enhanced understanding of this behavior pattern can be leveraged to reduce co-use in this population. Methods Connecticut AYAs (15–20 years old) who self-reported past-month nicotine and cannabis vaping participated in 1-hour focus groups examining of nicotine and cannabis use. Six focus groups were conducted in Spring 2023 (N = 29, mean group size n = 5). Data was analyzed with a two-stage deductive and inductive approach. Results Participants reported deliberate same session use in various modes (e.g., smoking, vaping). Same session use was most commonly reported to enhance positive psychoactive effects of cannabis (e.g., improve/enhance the high). Other common reasons were to reduce negative cannabis effects, such as vaping nicotine to reduce throat irritation or mask taste (e.g., vaping flavored nicotine product to mask cannabis taste). Some reported vaping nicotine so frequently that it unintentionally overlapped with cannabis use. Finally, other participants reported avoiding same session use as the combined psychoactive effects of nicotine and cannabis were too strong. Conclusion AYAs reported same session use primarily to enhance cannabis use experience (e.g., improving high or taste, reducing negative effects). Our findings indicate a complementary role of nicotine and cannabis, and suggest that prevention and cessation efforts for either substance need to address co-use behaviors.